Pengaruh Beban Kerja dan Kepemimpinan Terhadap Stres Kerja Serta Dampaknya Kepada Produktivitas Kerja Karyawan Divisi Produksi PT. Pupuk Kujang - Arni Kurniati; Yuli Mardianti (Jurnal Manajemen FE-UB, 2021)
The data used in this study are primary data obtained from the distribution of questionnaires toemployees of the Production Division of PT. Kujang Fertilizer. The data processing method uses the pathanalysis method with the help of the SPSS 24 program.The results showed that for sub-structure I: Workload directly affects work stress. Leadershipdirectly affects work stress. Research results for sub-structure II: Workload directly affects workproductivity. Leadership directly affects work productivity. Job stress directly affects work productivity.Workload indirectly affects work productivity through work stress. Leadership indirectly affects workproductivity through work stress.Keywords: Workload, Leadership, Work Stress, Productivity